2014
DOI: 10.1016/j.nbd.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E: Structure and function in lipid metabolism, neurobiology, and Alzheimer's diseases

Abstract: Apolipoprotein (apo) E is a multifunctional protein with central roles in lipid metabolism, neurobiology, and neurodegenerative diseases. It has three major isoforms (apoE2, apoE3, and apoE4) with different effects on lipid and neuronal homeostasis. A major function of apoE is to mediate the binding of lipoproteins or lipid complexes in the plasma or interstitial fluids to specific cell-surface receptors. These receptors internalize apoE-containing lipoprotein particles; thus, apoE participates in the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
471
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(484 citation statements)
references
References 151 publications
(300 reference statements)
6
471
0
7
Order By: Relevance
“…As described above, the core members among LDLR family include LDLR,VLDLR, LRP1, LRP1B, LRP4, LRP5, LRP6, megalin, Apoer2 and sorLA/LRP11, which are the confirmed ApoE receptors (16,38,39). In the current study, we found multifarious effects of E2 on LDLR family genes expression during osteoblast differentiation.…”
Section: Regulation Of Ldlr Family Core Members By E2 During Osteoblasupporting
confidence: 69%
See 2 more Smart Citations
“…As described above, the core members among LDLR family include LDLR,VLDLR, LRP1, LRP1B, LRP4, LRP5, LRP6, megalin, Apoer2 and sorLA/LRP11, which are the confirmed ApoE receptors (16,38,39). In the current study, we found multifarious effects of E2 on LDLR family genes expression during osteoblast differentiation.…”
Section: Regulation Of Ldlr Family Core Members By E2 During Osteoblasupporting
confidence: 69%
“…ApoE regulated bone metabolism in mice is possible due to uptake of lipid and lipid soluble vitamins such as vitamin K into osteoblasts (10). It is a common pattern of receptor-mediated endocytosis by the apoE receptors including the LDLR family and HSPGs, for apoE mediated uptake of lipid particles into target cells such as osteoblasts (14)(15)(16). Generally, apoE mediates the interaction of apoE-containing lipoproteins and lipid complexes with the LDLR family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression of apoE4 in the brain is the major genetic risk factor for early onset Alzheimer's disease (9,10). ApoE4 leads to reduced clearance of extracellular amyloid plaque deposits in the brain (10), increases neuronal degeneration (11), and reduces longevity (12). It is known that apoE can bind to amyloid-β peptide (13), but further mechanistic detail is lacking.…”
mentioning
confidence: 99%
“…[10][11][12] It has three major isoforms (Apo E2, Apo E3, and Apo E4) with different effects on lipid and neuronal homeostasis. 13 Intracellular Apo E may regulate various cellular processes physiologically or pathophysiologically. Apo lipoprotein (Apo) E is a multifunctional protein as it intervenes the binding of lipoproteins or lipid complexes in the plasma or interstitial fluids to specific cell-surface receptors as a major function of Apo E. 13 Role of Apo E and superoxide dismutase in patients with obstructive lung diseases Research Ali Mansoor Jasim Al-Ameri et al…”
Section: Apo Lipoproteine Ementioning
confidence: 99%